Gymnastic Frequency And Insomnia Level In Elderly At Bhakti Luhur Nursing Home Tropodo - Batara, Gabriela R; Maramis, Willy F; Erikavitri, Erikavitri (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2019)
Background: Aging is a natural process that cannot be avoided and this process will cause body changes in the elderly which leads to degenerative problems, one of them is sleep disorder. Increasing sleep hygiene is one of many ways to reduce sleep disorder. Sleep hygiene is the life style of the elderly that cause better sleep quality. Gymnastic in the elderly is a mild aerobic excercise that increases parasimpatic activity that leads to adrenalin, norepinephrine, catecolamin level decreasing and vasodilatation of blood vessels, these will cause oxygen transport throughout body, especially brain to lower blood pressure and causing relax effect and increasing the need of sleep in the elderly. Aim: This study goal is to examine the correlation between gymnastic frequency and insomnia level in elderly at Panti Werdha Bhakti Luhur Tropodo. Method: This study is an analytic study with the cross-sectional design and purposive sampling method. The primary data has been taken for 4 days from July 24 until 28, 2017 by: 1) using valid and reliable questionnaires about demographic data, level of insomnia, and cognitive status; 2) the secondary data for gymnastic frequency has been taken from April to June 2017. The study using the Spearman test. Result: The result showed the value of p=0,79, it can be concluded that there is no significant correlation between gymnastic frequency and insomnia level in elderly.